IMPROVING THE INTENSITY OF MATHEMATICS BASED ON MODERN TECHNOLOGIES AND ITS EFFICIENCY - Mullayeva Shahzodakhon (Bright Mind Publishing, 2025)
In this article, the effectiveness of intensive and innovative technologies in mathematics is covered by the efficiency of students and their positive impact on the education of students and the place in the teacher's pedagogical career. The study analyzes opportunities for the formation of mathematical computers on the basis of modern classes, digital means, and interactive approaches.
Keywords: Mathematical Education, Intensive Technologies, Innovative Methods, Interactive Teaching, Student Activity, Digital Tools, Efficiency of Education.